Prevalence of syphilis in female sex workers in three countryside cities of the state of Pará, Brazilian Amazon - de Souza, Ronaldo Lopes (BMC Infect Dis, 2020)
BACKGROUND: Syphilis is a sexually transmitted infection (STI) transmitted from person to person mainly by sexual intercourse or through vertical transmission during pregnancy. Female sex workers (FSWs) are exposed especially to syphilis infection, and besides all the efforts to control the spread of STIs, syphilis prevalence is still rising, mainly occurring in low-income countries. This study aimed to investigate the syphilis prevalence, demographic characteristics and sexual habits among FSWs in the Amazon region of Brazil. METHODS: A cross-sectional study was carried out including 184 FSWs from 3 countryside cities of the state of Pará, Amazon region of Brazil. A venereal disease research laboratory test and an indirect immunoenzyme assay to test antibodies against Treponema pallidum were used for screening syphilis infection, while sexual habits and demographic data information were collected through a semi-structured questionnaire. Data was analyzed comparing groups with/without syphilis. Poisson regression models were used to estimate the reasons of prevalence (RP). RESULTS: The overall prevalence of syphilis was 14.1% (95% CI = 9.8–17.8). FSWs had between 15 and 56 years of age, most were unmarried (65.7%), had attended less than 8 years of formal education (64.1%), had between 10 and 20 partners per week (64.1%), and reported no previous history of STIs (76.1%) and regular use of condom (52.7%). Low level of education attending up to the primary school (RP adjusted = 3.8; 95% CI = 1.4–9.2) and high frequency of anal sex during the past year (RP adjusted = 9.3; 95% CI = 3.5–28.7) were associated with a higher prevalence of syphilis. CONCLUSIONS: A high prevalence of syphilis among FSWs in the Brazilian Amazon region was identified, showing that syphilis is more likely to be transmitted in FSW working in low-income areas, which is attributed to the low level of education. Anal intercourse was found as a risk factor associated with syphilis. Health programs focused on risk populations appear as a rational way to control syphilis spread, which is a rising problem in Brazil and in other several countries.